Demazure Modules, Chari–Venkatesh Modules and Fusion Products - Ravinder, B. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
Let g be a finite-dimensional complex simple Lie algebra with highest root θ. Given two non-negative integers m, n, we prove that the fusion product of m copies of the level one Demazure module D(1,θ) with n copies of the adjoint representation ev₀V(θ) is independent of the parameters and we give explicit defining relations. As a consequence, for g simply laced, we show that the fusion product of a special family of Chari-Venkatesh modules is again a Chari-Venkatesh module. We also get a description of the truncated Weyl module associated to a multiple of θ.